The left parietal and premotor cortices: motor attention and selection. - Rushworth, M; Johansen-Berg, H; Göbel, S; Devlin, J (2003)
It is well established that the premotor cortex has a central role in the selection of movements. The role of parts of the parietal cortex in movement control has proved more difficult to describe but appears to be related to the preparation and the redirection of movements and movement intentions. We have referred to some of these processes as motor attention. It has been known since the time of William James that covert motor attention can be directed to an upcoming movement just as visuospatial attention can be directed to a location in space. While some parietal regions, particularly in the right hemisphere, are concerned with covert orienting and the redirecting of covert orienting it may be useful to consider other parietal regions, in the anterior inferior parietal lobule and in the posterior superior parietal lobule, particularly in the left hemisphere, as contributing to motor attention. Such parts of the parietal lobe are activated in neuroimaging experiments when subjects covertly prepare movements or switch intended movements. Lesions or transcranial magnetic stimulation (TMS) affect the redirecting of motor attention. The difficulties apraxic patients experience when sequencing movements may partly be due to an inability to redirect motor attention from one movement to another. The role of the premotor cortex in selecting movements is also lateralized to the left hemisphere. Damage to left hemisphere movement selection mechanisms may also contribute to apraxia. If, however, it remains intact after a stroke then the premotor cortex may contribute to the recovery of arm movements. A group of patients with unilateral left hemisphere lesions and impaired movements in the contralateral right hand was studied. Functional magnetic resonance imaging showed that in some cases the premotor cortex in the intact hemisphere was more active when the stroke-affected hand was used. TMS in the same area in the same patients had the most disruptive effect on movements. In summary, patterns of motor impairment and recovery seen after strokes can partly be explained with reference to the roles of the parietal and premotor cortices in motor attention and selection.